DEVELOPMENT OF COMORBID CONDITIONS UNDER THE INFLUENCE OF DRUGS USED IN RHEUMATOLOGY - Muratova Muyassar Medetbayevna; Poʻlatova Niginabonu Oʻtkir qizi; Ibrohimova Dilrabo Ibrohim qizi; Gʻulomova Shaxnoza Xurshid qizi; Yermaxamatov Ulugʻbek Dauletovich; Sadullayeva Xolniso Ulugʻbek qizi (Western European Studies, 2024)
In modern rheumatology, the problem of comorbid infections has not lost its importance. Especially in recent years, the introduction of genetically engineered biological drugs into practice has increased. As a result, the risk of various local comorbid infections, including opportunistic infections - invasive mycosis, pneumocystic pneumonia, and urinary tract infections has increased. In addition, reactivation of latent infections in the body - tuberculosis infection, hepatitis B and C viruses is observed. This required the study of comorbid infections in rheumatological diseases based on clinical rheumatological anamnesis and retrospective analysis. As a result, in which rheumatological diseases comorbid infection is more common; which comorbid infection is observed more often; which group has an increased occurrence of comorbid infections after taking drugs; it was possible to analyze the occurrence of comorbid infection in patients by age and gender. In the conclusion, the importance of vaccination and necessary solutions to prevent the mutual influence of rheumatological diseases and comorbid infections was emphasized.
Keywords: rheumatological diseases; gene-engineered biological drugs; comorbid infections